Is educational differentiation associated with smoking and smoking inequalities in adolescence? A multilevel analysis across 27 European and North American countries. Issue 7 (23rd May 2016) - Rathmann, Katharina; Moor, Irene; Kunst, Anton E.; Dragano, Nico; Pförtner, Timo‐Kolja; Elgar, Frank J.; Hurrelmann, Klaus; Kannas, Lasse; Baška, Tibor; Richter, Matthias
Abstract: This study aims to determine whether educational differentiation (i.e. early and long tracking to different school types) relate to socioeconomic inequalities in adolescent smoking. Data were collected from the WHO‐Collaborative 'Health Behaviour in School‐aged Children (HBSC)' study 2005/2006, which included 48, 025 15‐year‐old students (Nboys = 23, 008, Ngirls = 25, 017) from 27 European and North American countries. Socioeconomic position was measured using the HBSC family affluence scale. Educational differentiation was determined by the number of different school types, age of selection, and length of differentiated curriculum at the country‐level. We used multilevel logistic regression to assess the association of daily smoking and early smoking initiation predicted by family affluence, educational differentiation, and their interactions. Socioeconomic inequalities in both smoking outcomes were larger in countries that are characterised by a lower degree of educational differentiation (e.g. Canada, Scandinavia and the United Kingdom) than in countries with higher levels of educational differentiation (e.g. Austria, Belgium, Hungary and The Netherlands). This study found that high educational differentiation does not relate to greater relative inequalities in smoking. Features of educational systems are important to consider as they are related to overall prevalence in smoking and smoking inequalities in adolescence.